Changes on shoulders flexibility with detraining: a case report - L.C. Ruberti; S. Gobbi; G. Christofoletti; R. Gonçalves (Desafio Singular, 2008)
The aim of this study was to verify the influence of a six-month detraining program on shoulders flexibility, after a period of specific training by means of a neuroprioceptive facilitation technique named as Scientific Stretching for Sport (3S). This research consists of a case report of a 62 year-old subject. First of all, the subject attended a 2-month period of flexibility training, by means of 3S technique. After that, the subject stayed away from the training for a period of six months. The flexibility was measured by goniometer, both at baseline (beginning of the detraining period) and six months after. The results showed decrease in flexibility on all the movements, except for right shoulder extension and medial rotation. A variety of putative mechanisms may explain the flexibility decrement with detraining, such as a reduction in conjuntive extensibility.